EFEKTIVITAS KOMUNIKASI OPINION LEADER PADA KELOMPOK TANI KARET DI KELURAHAN BATU BERSURAT KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - BENRI SIHITE; Roza Yulida; Yulia Andriani (Indonesian Journal of Agricultural Economics, 2023)
Opinion leader is a person who becomes an opinion leader in a group/sub-group. Opinion leaders in farmer groups are indicated by the presence of individuals who have more number of communication relationships than the average number of communication relationship of other individuals in the communication network. Interpersonal communication is considered the most effective in an effort to change a person’s attitude, opinion, or behavior because of its dialogical nature in the form of conversation. This study aims to examine the effectiveness of opinion leader interpersonal communication on rubber farmers in Batu Bersurat village, XIII Koto Kampar District, Kampar Regency. This research was used is descriptive analysis. The samples in this study were taken from the Sungai Kulim farmer group and the Sungai Gulamo farmer group, namely as many as 20 samples of members of the Sungai Kulim farmer group and as 22 samples of members of the Sungai Gulamo farmer group with a total sample of 42 samples. The results showed that interpersonal communication between actors IW, YS and AU with independent rubber farmers in Batu Bersurat Village was effective. Communication between IW, YS and AU actors and farmers is very well established, this supported by an open attitude to each other, mutual respect (positive behavior) and mutual support (supportive) in the application of information related to rubber development. Actors IW, YS and AU as opinion leaders have empathy for independent rubber farmers in Batu Bersurat Village and feel there is no difference between them.